Thyroid hormones and neurological impairments during the first two days after stroke: A pilot study - Kobra Akhoundzadeh; Ashraf Zarvani; Fatemeh Mohajerani; Sakineh Shafia (Heliyon)
Despite plenty of studies on the change in thyroid hormones after stroke, there is still no consensus for a comprehensive conclusion and clinical application. This pilot study aimed to investigate the change in thyroid hormones and its association with neurological impairments during the first two days after the stroke. This was a cross-sectional descriptive and analytical study. Neurological deficits were assessed using the National Institutes of Health Stroke Scale (NIHSS). In addition, blood samples were collected for TSH, T3, and T4. P value < 0.05 was considered significant. Fifty patients (42 % men) with a mean age of 69.73 (SD ± 12.31) were included. The majority of patients had a high level of TSH and T4, and a normal level of T3 on the first and second days of hospitalization. 33.3 and 20.9 percent of patients had NIHSS scores >10 on the first and second day respectively. According to the multivariate analysis, high T4 hormone was as a predictor of NIHSS score >10. There was no association between thyroid hormones and NIHSS at the admission. In addition, there was no relationship between thyroid hormones and TSH on the second day. According to the results, stroke affects the levels of thyroid hormones and the pituitary–thyroid axis. Because of the diversity in results of existing studies, further clinical research with the same methodology and data analysis is needed to find consistent results on the association between thyroid hormones and neurological impairments. Monitoring thyroid status in stroke patients may be recommendable.